IMPLEMENTASI AKUNTANSI PERSEDIAAN BERDASARKAN SAK EMKM PADA TOKO CB ECEK - Deviana Eka Nur Rahmawati; Akhmad Naruli; Miladiah Kusumaningarti (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Implementing inventory accounting is very important for inventory management and can ensure product availability to meet customer demand, especially at the CB ECEK Store. This research aims to implement inventory accounting based on SAK EMKM at CB ECEK Stores related to inventory recognition, measurement and presentation. This research uses primary data obtained from sales and purchase data on merchandise inventory at the CB ECEK Store for the period 1 July – 31 December 2023. The data in this research was obtained from interviews and documentation. The sampling technique in this research was purposive sampling so that 10 merchandise inventories were collected that met the criteria, including rear sweets, battery pangkon, speedo cover, skok seat, tank pangkon, footstep pangkon, frame ring, CB mudguard rubber, seat pangkon, middle spring. This research uses a quantitative approach with descriptive methods. The results of this research show that acquisition costs are recognized only at the purchase cost, so there is a difference in acquisition costs after shipping costs or transportation costs are included. Calculation of inventory cards using a perpetual system with the MPKP valuation method shows that ending inventory in December was recorded at IDR 1,804,800 and profit at the end of the period was recorded at IDR 5,671,300. Based on the research results, CB ECEK Stores have not implemented inventory accounting based on SAK EMKM, because acquisition costs are still recognized at the purchase price only, the merchandise inventory valuation method does not use the MPKP or Weighted Average method, and the inventory of goods has not been presented in the financial statements.